1994
DOI: 10.1002/pon.2960030205
|View full text |Cite
|
Sign up to set email alerts
|

A randomized study of a rehabilitation program for cancer patients: The ‘starting again’ group

Abstract: This study compares, in a prospective randomized design, a rehabilitation ‘Starting again’ program for cancer patients (n = 98) and a control condition (n = 101). Assessments were carried out pre‐ and post‐intervention and at a 3 months follow‐up. The program consisted of 11 structured, two‐hour sessions run for a period of seven weeks by an oncology nurse specialist assisted by experts in various fields. The contents focused on physical training, information and coping skills training. Patients in the ‘Starti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
78
0
2

Year Published

1995
1995
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(86 citation statements)
references
References 16 publications
6
78
0
2
Order By: Relevance
“…Concerning mood, as reflected by short-POMS, there were no significant differences as in improvement (beforeafter), this finding is in good agreement with similar studies (7,22,25), i.e. patients are satisfied and content with the educational groups, their perceived knowledge has increased, but this is not reflected in specific variables such as 'anger' or 'energy', and so on.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Concerning mood, as reflected by short-POMS, there were no significant differences as in improvement (beforeafter), this finding is in good agreement with similar studies (7,22,25), i.e. patients are satisfied and content with the educational groups, their perceived knowledge has increased, but this is not reflected in specific variables such as 'anger' or 'energy', and so on.…”
Section: Discussionsupporting
confidence: 80%
“…Furthermore, patients in the control group perceived that their knowledge had increased with time but the difference was significantly greater for the interventional group. Berglund et al showed in their studies (7,22) that patients in the rehabilitation programme were more satisfied than controls. The experiences from other education groups are similarly positive (23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…75,78,79 -86 Strength-training components were included in two studies. 76,77 On-site supervised exercise has been the norm for patients who were receiving chemotherapy or RT, 74,84 although a few researchers have studied the effects of home-based programs. 74,75,83 Nearly all the interventions were offered independent of the healthcare provider with the exception of on-site physician supervision of exercise among patients who had completed bone marrow transplants.…”
Section: Exercise Interventionsmentioning
confidence: 99%
“…La mayoría de trabajos realizados hasta el momento son intervenciones cortas, entre 6 y 10 sesiones semanales, e incluso se han realizado intervenciones grupales de fin de semana, que trabajan diferentes temas relacionados con la enfermedad, como la ansiedad, los miedos, la comunicación con el entorno, la autoestima, etc. (28)(29)(30)(31) . El objetivo del presente estudio es conocer la evolución emocional que siguen las pacientes con cáncer de mama, participantes en una intervención grupal de larga duración, concretamente a lo largo de 8 meses (20 sesiones), a fin de observar la posible eficacia de la terapia en la mejora de las emociones negativas o desadaptativas.…”
Section: Introductionunclassified